FORMAÇÃO CONTINUADA DE PROFESSORES NA EDUCAÇÃO INFANTIL: Facilidades e fragilidades para a inclusão escolar de crianças com transtorno do espectro autista - PINTO, Daniele Santos (2025)
The inclusion of children with disabilities in regular education, especially in Early Childhood Education, is a challenge that requires ongoing training for teachers, considering that at this stage children have varied learning rhythms and require specific methodologies that respect their particularities. Teaching a child with autism spectrum disorder requires a deep understanding of their main characteristics, frequent behavioral patterns and areas that require more attention, among other aspects. Therefore, the teacher needs to be qualified to offer a structured, intentional and adaptable education, focusing on the acquisition of knowledge, intellectual and psychomotor skills, as well as diverse attitudes. The general objective of this study was to analyze how ongoing training for teachers in early childhood education occurs for the inclusion of children with autism spectrum disorder in regular education. This was a descriptive, exploratory and qualitative field study carried out at the Maria José Serrão Elementary School in São Luís. The participants were 9 Early Childhood Education teachers who work with students with autism spectrum disorder, support levels 1 and 2, and who had at least one year of experience with these children. To collect the data, semi-structured interviews were conducted in person and individually, on previously scheduled days and times, according to the availability of each participant. Content analysis was used to interpret the data. The results indicated that the school is offering continuing education under the responsibility of the management. The pedagogical coordinator facilitates this training for teachers through several strategies, aiming to stimulate the interest of teachers in professional development, in addition to addressing other issues related to the dynamics of work during the additional hours on Saturdays. During the study, it was observed in the statements of the participants the need for more targeted and less broad training, so that the particularities of children with autism spectrum disorder are understood and valued. This ensures the implementation of strategies and practices that foster an inclusive environment, as well as interventions that favor their development and learning. It is concluded that there is a need for more effective planning of future continuing education programs on the topic in question.